2009
DOI: 10.1159/000235808
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive Lumbar Punctures as Treatment for Normal Pressure Hydrocephalus

Abstract: Selected normal pressure hydrocephalus (NPH) patients cannot be treated by shunt operation because of the procedure’s high complication rate. We have treated cases in which prolonged clinical improvement of NPH was experienced after one or two lumbar punctures (LPs). We evaluated the predictors of prolonged improvement of NPH symptoms by repeated LP. Thirty-one NPH patients were retrospectively evaluated (age 72.5 ± 5.8 years). Gait disturbance, urinary incontinence, and cognitive impairment were semiquantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…As the disease progresses and the ventricles get larger, they may lose elasticity12). If the ventricles are slightly shrunken by CSF removal, the elasticity of the ventricles may recover along with symptomatic improvement over a certain period12).…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses and the ventricles get larger, they may lose elasticity12). If the ventricles are slightly shrunken by CSF removal, the elasticity of the ventricles may recover along with symptomatic improvement over a certain period12).…”
Section: Discussionmentioning
confidence: 99%
“…Traitement par PL déplétives répétées. Une alternative au traitement chirurgical proposée par Lim et al [52] en 2009 serait la répétition de PL déplétives. Selon cette étude, une ou deux PL déplé-tives pourraient suffire à maintenir une efficacité clinique allant au-delà d'un an après la ponction.…”
Section: Le Dosage Des Biomarqueurs Dans Le Lcrunclassified
“…The disease dates back to the time of Hippocrates when he described a "liquefaction of the brain" that showed symptoms such as headache, vomiting, and visual impairment [109]. Other symptoms can include high intracranial pressure, in addition to impairments in gait, cognition, alertness, and continence [110]. Although this disease can have various causes, it has been shown that there is a higher prevalence of hydrocephalus in patients that are known to have ciliary defects, and the disease can also be linked to genes known to impact cilia function or structure [111].…”
Section: Hydrocephalusmentioning
confidence: 99%
“…In elderly patients shunt implantation is very risky. Repeated lumbar puncturing in patients with communicating hydrocephalus can potentially prevent the need for shunt surgery in these patients [110]. The newest addition to shunt technology is antibiotic-impregnated shunts that help prevent post-surgical infections [128].…”
Section: Hydrocephalusmentioning
confidence: 99%